Constitutional interpretation and Constitution substitution: oscillating between the juridical and the political - García López, Luísa Fernanda (Revista de Investigações Constitucionais, 2020)
The concept of constitution substitution is a notion that has not been developed by constituent power, and in that measure, the Colombian Constitutional Court has established a precedent for the amendment process of the Legislative Act, which is performed by congress in order to limit the power of constituted power. In spite the fact that the Court has stated that there are no clauses written in stone, it has forged some fundamental principles and consolidated the defining axes, is what resume the theory of substituting. However, constitutional amendments have some limits to what Richard Albert makes a reference and summarize in 4 fundamental characteristics, that should not exceed the constitutional scope. As was pointed out by Albert the power to amend is one above all that does not exceed the scope of what was intended in the constitution, but there may be an intermediate point which he calls dismemberment, which is more than an amendment but does not get to become a structural reform of the constitution. Let’s see how Colombia’s Constitution and the Constitutional Court have set limits to constitutional amendments and exceeded constitutional limits through dismemberment.